Design of E-plane T-junction dividers using substrate integrated waveguide (SIW) - Aram, Ido; Garb, Khona; Kastner, Raphael (2014 IEEE 28th Convention of Electrical & Electronics Engineers in Israel (IEEEI), 2014)
Power dividers/combiners are critical building blocks of Solid State Power Amplifiers (SSPA). We propose a novel E-plane power divider with arbitrary splitting ratios, implemented in SIW technology. The divider is realized on standard dual layered PCB substrates, where the required coupling is achieved through a slot between the two layers. This unique design can be subject to easy modifications that support arbitrary power split ratios. Both equal and non-equal K-Band power splitter prototypes have been designed, fabricated and tested. Simulation and experiments validate the performance of this very useful building block for future miniature SSPA's.